Analysis of possibility of hydrometallurgical processing of lead-containing sludges - Кубякіна, Ольга Вадимівна; Косенко, Вікторія Миколаївна (Eastern-European Journal of Enterprise Technologies, 2014)
The main world trends of obtaining lead by processing lead-containing dust were studied, the main advantages and disadvantages of these methods were defined. The composition of coarse and fine dust, which is formed during lead raw material smelting and essential elements, which are lost with them, was given. It was found that the low-temperature processes, i.e. sludge processing using hydrometallurgical methods are the most promising for fusible and toxic lead. The method, which consists of two stages of sludge processing: hydrometallurgical and pyrometallurgical, was proposed. A thermodynamic analysis of the process under study was carried out, the results of which showed that conducting the process of lead-containing sludge processing according to the given technology improves the cost-effectiveness of the process by reducing costs for equipment and electric heating.